Startups no ecossistema mineiro de inovação – estudo em empresas de Belo Horizonte - Bárbara Graciano de Oliveira (2019)
This study has identified startups profile that compose innovation ecosystem considering a cut with companies participating in the TECHMALL S/A Acceleration Program located at Belo Horizonte, Minas Gerais state. The methodological approach was descriptive-qualitative identifying general aspects of the company, skills and team profile, challenges faced, existence of indicators, degree of innovation and experience in acceleration programs. Data collection occurred by using an electronic form applied to 14 active startups. The results obtained indicate, in general, that the difficulties faced by the most startups were "initial capital available to the business", "customer acquisition", "access to available financing in the market", "investment scarcity" and to "scale sales". Most of them deals with incremental innovation, and the main types of intellectual property generated were trademark registration, patent filing and software registration. The Acceleration Program experience has indicated the factors that motivated the entrepreneur choice about TECHMALL, the aspects explored by the accelerator and those that could have been more explored in the vision of the CEOs. This dissertation final results contain references capable of contributing to the Minas Gerais’ innovation ecosystem aiming to act on possible difficulties in the relationship between the public sphere and the private initiative to encourage the development of companies of this nature. The study suggests that startups and the innovation ecosystem agents further tighten dialogue, as well as the possibility of adopting fiscal, legal and administrative measures that favor local entrepreneurship.